Diffuse Leptomeningeal Oligodendrogliomatosis in a Cow. Issue 2 (March 2020) - Kauer, Ronja V.; Bagatella, Stefano; Oevermann, Anna
A 4.5-year-old cow showing neurological signs consistent with predictors of bovine spongiform encephalopathy (BSE) was investigated as a potential BSE-suspect case and proved to be negative. Macroscopic analysis revealed a tan neoplastic mass growing along the leptomeninges of the caudal brain and extending into the third (III) ventricle without significantly involving the neuroparenchyma. Pathological features (uniform round hyperchromatic neoplastic cells embedded in abundant myxoid matrix, microcysts, microvascular proliferation) and diffuse Olig2 expression were most consistent with diffuse high-grade leptomeningeal oligodendrogliomatosis. In line with former reports of extensive leptomeningeal involvement in bovine oligodendroglioma, this report suggests that bovine oligodendroglial tumors have a strong propensity to grow within the leptomeningeal space. In addition, it indicates that Olig2 is a useful marker to confirm glial lineage in formalin-fixed, paraffin-embedded bovine tissue.